Security of contract and the pursuit of fairness - PHANG, Andrew (Institutional Knowledge at Singapore Management University, 2000)
Paper presented at 10th Annual Journal of Contract Law Conference Auckland 22 November 1999 - security of contract should only be pursued if it leads to a fair result - a dogmatic adherence to certainty is an anathema to modern law - focus on fairness is an integral part of the law of contract - classical natural law theory provides a reasonable basis to justify incorporation of objective fairness into contract law.